Yogic practices for dyslipidemia in type 2 diabetes mellitus: A systematic review of randomized-controlled trials - Bandana Sairem; Khushbu Jain (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Diabetes ranks third and tenth among both men and women, respectively, in terms of probable causes of life loss. It has been linked to a variety of cardiovascular problems, including hypertension, dyslipidemia, neuropathy, and more. Diabetic dyslipidemia is one of the main factors that contribute to coronary artery disease fatalities. The use of pharmaceuticals to treat these conditions has a number of negative consequences. People are looking for alternatives to traditional treatments that have no or few adverse effects. Yoga is a comprehensive wellness technique that emphasizes both the body and the mind. Yoga has been shown in multiple clinical studies to reduce the risk of Type 2 diabetes and associated complications, such as hypertension and dyslipidemia. The review's goal is to synthesize all relevant research findings. METHODS: Data were gathered through a stepwise search method that used keywords to search the online PubMed, Google Scholar, and Cochrane library databases. RESULTS: After examining the databases for 76 potentially relevant papers, six randomized-controlled trials that met the inclusion and exclusion criteria were chosen. The number of participants ranged from 20 to 231, with Yoga sessions lasting from 10 days to 24 weeks. Studies have revealed a good lipid profile as well as other diabetes-related markers such as fasting blood glucose and postprandial blood glucose after Yogic interventions most of which includes Surya Namaskara, Asana such as Pawanmuktasana, Bhujangasana, Ardha matsyendrasana, Pranayama, and Meditation. CONCLUSIONS: Yogic practices such as Surya namaskara, Pawanmuktasana, Bhujangasana, and Ardha matsyendrasana along with the practices of pranayama and meditation appears to have a favorable effect on lipid profiles in people with type 2 diabetes.